ANALISIS KONFLIK SOSIAL ANGGOTA KARANG TARUNA â€œBUNGE SERAMPAIâ€ DI DESA MAKRAMPAI KECAMATAN TEBAS - Kalijar,, Hidayat; Budjang, Gusti; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe title of this research is the analysis of social conflict of the members of "bunge serampai" youth group in Makrampai Village, Tebas District. Common problem in research this is how the analysis of social conflict of the members of "bunge serampai" youth group in Makrampai Village, Tebas District. With sub problems (1) The causes of social conflict of the members of "bunge serampai" youth group in Makrampai Village, Tebas District? (2) The impact of social conflict of the members of "bunge serampai" youth group in Makrampai Village, Tebas District? The results of this research is (1) The differences in form of the differences between individuals and divergence of interests is a major factor of social conflict is happening in the members of "bunge serampai" youth group in Makrampai Village, Tebas District. It is because perpetually go put on going on between youth Sutra dan Sebindang hamlet. (2) As a result of the occurrence of the conflict caused by the differences between individuals and the difference of such interest, there has been a state of functional and dysfunctional during the conflict has lasted. The state of functional formed as a result of social unrest in the members of "bunge serampai" youth group in Makrampai Village, Tebas District is increase strong solidarity each group engage in conflict that is youth Sutra and Sebindang hamlet. While the state of dysfunctional due to social unrest in the area are the affliction and ruin of unity group of the members of "bunge serampai" youth group in Makrampai Village, Tebas District.Â Keywords: Social Conflict, Youth Group